Compliance with referral of sick children: a survey in five districts of Afghanistan - Newbrander William; Ickx Paul; Werner Robert; Mujadidi Farooq (BMC, 2012)
Abstract Background Recognition and referral of sick children to a facility where they can obtain appropriate treatment is critical for helping reduce child mortality. A well-functioning referral system and compliance by caretakers with referrals are essential. This paper examines referral patterns for sick children, and factors that influence caretakers' compliance with referral of sick children to higher-level health facilities in Afghanistan. Methods The study was conducted in 5 rural districts of 5 Afghan provinces using interviews with parents or caretakers in 492 randomly selected households with a child from 0 to 2 years old who had been sick within the previous 2 weeks with diarrhea, acute respiratory infection (ARI), or fever. Data collectors from local nongovernmental organizations used a questionnaire to assess compliance with a referral recommendation and identify barriers to compliance. Results The number of referrals, 99 out of 492 cases, was reasonable. We found a high number of referrals by community health workers (CHWs), especially for ARI. Caretakers were more likely to comply with referral recommendations from community members (relative, friend, CHW, traditional healer) than with recommendations from health workers (at public clinics and hospitals or private clinics and pharmacies). Distance and transportation costs did not create barriers for most families of referred sick children. Although the average cost of transportation in a subsample of 75 cases was relatively high (US$11.28), most families (63%) who went to the referral site walked and hence paid nothing. Most caretakers (75%) complied with referral advice. Use of referral slips by health care providers was higher for urgent referrals, and receiving a referral slip significantly increased caretakers' compliance with referral. Conclusions Use of referral slips is important to increase compliance with referral recommendations in rural Afghanistan.